Stripping/flocculation/membrane bioreactor/reverse osmosis treatment of municipal landfill leachate - Hasar, Halil; Unsal, Sezahat A.; Ipek, Ubeyde; Karatas, Serdar; Cinar, Ozer; Yaman, Cevat; Kinaci, Cumali (Elsevier, 2009)
This study presents a configuration for the complete treatment of landfill leachate with high organic and ammonium concentrations. Ammonia stripping is performed to overcome the ammonia toxicity to aerobic microorganisms. By coagulation-flocculation process, COD and suspended solids (SS) were removed 36 and 46%, respectively. After pretreatment, an aerobic/anoxic membrane bioreactor (Aer/An MBR) accomplished the COD and total inorganic nitrogen (total-N-i) removals above 90 and 92%, respectively, at SRT of 30 days. Concentrations of COD and total-N-i (not considering organic nitrogen) in the Aer/An MBR effluent decreased to 450 and 40 mg/l, respectively, by significant organic oxidation and nitrification/denitrification processes. As an advanced treatment for the leachate, the reverse osmosis (RO) was applied to the collected Aer/An MBR effluents. Reverse osmosis provided high quality effluent by reducing the effluent COD from MBR to less than 4.0 mg/l at SRT of 30 days. (C) 2009 Published by Elsevier B.V.
Keywords: Leachate; Ammonia toxicity; Pretreatment; Aerobic/anoxic MBR; Reverse osmosis